RELEVANCE OF JUSTICE AND EQUALITY IN AMBEDKAR THOUGHT - Singh, Sanjana; Khande, Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ambedkar, the chief architect of the Indian Constitution, was a leading thinker and social reformer whose vision was centered on justice and equality. His philosophy was deeply influenced by his personal experiences of caste-based discrimination, political philosophy, constitutionalism, social justice and his interaction with scholars. In contemporary society where social and economic inequalities persist despite legal safeguards, Ambedkar’s ideas are highly relevant. At the core of Ambedkar’s philosophy is the idea that justice should be social, economic and political. He believed that political democracy is incomplete unless complemented by social and economic democracy. His advocacy for affirmative action, labour rights, women’s empowerment and the destruction of caste discrimination was rooted in his vision of an egalitarian society where every individual, regardless of gender, had access to dignity, education and economic opportunities. An emphasis on constitutional morality was another important aspect of his philosophy. He argued that true justice could only be achieved when society followed the moral principles embedded in the Constitution rather than traditional hierarchies. The Fundamental Rights and Directive Principles of State Policy in the Indian Constitution reflect his commitment to justice, and ensure that marginalised communities receive legal protection and access to opportunities for development and representation. According to these constitutional provisions, social inequality, economic inequality and gender injustice manifest in caste-based discrimination. Dalits, Adivasis and marginalised groups still face exclusion, inadequate educational and employment opportunities and socio-political discrimination. Ambedkar’s vision is important in addressing these systemic challenges. His call to "educate, agitate, organise" inspires movements advocating for the rights of oppressed communities. His work is studied globally in discussions on human rights, discrimination, and political representation. His ideas serve as a blueprint for those seeking to build an inclusive and democratic society. Justice and equality, in Ambedkar’s view, are not merely legal concepts but fundamental social imperatives. His vision urges enlightened individuals of society to move beyond symbolic reforms and work towards real change by ensuring equal access to rights, opportunities, and dignity for all individuals. As long as oppression and discrimination exist, Ambedkar’s philosophy will remain a guiding force for achieving social justice.